Penguatan Kelembagaan Sosial – Ekonomi Desa Melalui BUMDes Panggung Lestari di Desa Panggungharjo, Kecamatan Sewon Kabupaten Bantul - Teguh Budi Prasetya; Niken Widyastuti (HOME, 2020)
BUMDes is an institution managed by the community and village government to strengthen the village economy and is formed based on the needs and potential of the village. BUMDes performance must make a significant contribution to improving the welfare of citizens. This study aims to find out how the Government of Panggungharjo Village, Bantul Regency in Strengthening Village Institutions (BUMDes). The method in this research is qualitative descriptive research and research results emphasizing the meaning of generalization. BUMDes Panggung Lestari, Panggungharjo Village as an effort to utilize the potential of the village has become an entity and can lift the economy of its community by establishing economic business development and social services, and establishing BUMDes institutional strengthening programs